Sistem Pendukung Keputusan Pemberian Penghargaan Karyawan Terbaik dengan Metode Topsis (Studi Kasus PT. PP London Sumatra Indonesia, Tbk) - Veri Yanto (Yayasan Kita Menulis, 2019)
Abstract-Award is a reward given in material and non-material given by the company to its employees so that they can work with high motivation and achievement in achieving company goals. To build a decision support system for awarding and using the Topsis method, several criteria include Absence, Behaviour, Discipline, Responsibility, Achievement. One of the methods used to resolve problems in awarding is the Topsis method (Technique for Order Preference by Similiarity).. The TOPSIS method is a multi-criteria decision making method that uses the principle that the chosen alternative must have the closest distance to the positive ideal solution and the farthest distance to the negative ideal solution. the process of determining the positive ideal solution and the negative ideal solution, the process of calculating the distance of each alternative to the ideal solution, and the process of calculating the preference value of each alternative. The results of the TOPSIS method calculation process are in the form of information determining the awarding.